Nephro Defensive Efficiency of Cichorium Intybus Against Toxicity Caused by Copper Oxide Nanoparticles - Fidan Fikrat Ahmed, Ozdan Akram Ghareeb, Ayoub Ali Hussein Al-Bayti (Pakistan Journal of Medical & Health Sciences, 2022)
The penetration of nanotechnology into the medical world is constantly growing, and this raises concerns about its toxicity. This study aimed to illustrate the defense ability of Cichorium intybus (CI) against the nephrotoxicity induced by copper oxide nanoparticles (CuONPs) in a rat model. 32 laboratory rats were evenly distributed into 4 groups, each containing 8 animals. CON rats did not receive any dosage, whereas, CuONPs animals were dosed with copper oxide nanoparticles. As for the CuONPs + CI group, intoxicated rats were dosed with Cichorium intybus extract. Lastly, CI rats were given C.intybus extract only. The parameters of renal function, oxidative stress, and renal histological changes were measured. Animals treated with CuONPs showed negative changes in all examined parameters of kidneys compared to the CON group. However, co-administration of plant extract with NPs showed a clear improvement effect of these toxic changes. We concluded that the high dose of CuONPs causes significant kidney damage, and CI extract has a defensive effect against this toxicity.